Desarrollo de una herramienta para la asignación de turnos de trabajo de los días sábados y festivos en el área Customer Experience de la empresa Mercado Libre Colombia Ltda. (2020)
In the present project the knowledge acquired in the course of the industrial engineering degree were integrated to carry out a computational tool in order to facilitate the assignment and visualization of the work shifts for Saturdays and holidays of the representatives on duty tomorrow and intermediate shifts, of the company MercadoLibre Colombia LTDA. For this, there are four chapters in which a diagnosis was started where the different levels of the organizational environment are analyzed, this mainly consists of global issues of e-commerce and shift allocation. For the second chapter, the variables were parameterized for the allocation of shifts, in addition to this, the respective survey is carried out, where the respondents express the aspects to be improved in the current way in the distribution of shifts and their visualization, with The results of this survey and the parameterization given above have the bases with which to proceed to program the respective tool.